Effective safety propaganda: A study in South African industry - J. Fisher; R. Parry (South African Journal of Business Management, 1985)
In this study a safety propaganda programme was designed, introduced, monitored, and analysed in the context of ongoing industrial activity. Pre-experimental investigations revealed areas of unsafe activity which were then subjected to the experimental safety propaganda material. Results showed that in a number of workshops studied the propaganda had a positive effect in terms of a reduction in the number of unsafe incidents. Ancillary findings showed wide differences in the formal and informal attitudes expressed by both managerial and supervisory grades towards simple safety situations. It is suggested that such inconsistency is unlikely to be conducive to a stable behavioural commitment to safety procedures.
Keywords: 650